Along a River. The First French-Canadian Women. - Grenier, Benoît (Labour / Le Travail, 2014)
The article reviews the book, "Along a River. The First French-Canadian Women," by Jan Noel.
Keywords: ALONG a River: The First French-Canadian Women (Book); Canada; FRENCH-Canadians; History; NOEL, Jan; Nonfiction; Women